(untitled) (Bangladesh Journal of Botany, 2025)
To bolster food security in the Loess Plateau, the Chinese government initiated a land expansion program (2013-2017) targeting a 337.80 km2 increase in cultivated area through integrated ditch management and reclamation. Given the region’s reliance on rain-fed agriculture, optimizing production under climate change is critical for evidence-based policymaking. This study evaluates climate and fertilization impacts on spring maize yields using the APSIM model under two Shared Socioeconomic Pathways SSP1-2.6 (sustainable low-emission development) and SSP5-8.5 (fossil-fueled high-emission development). Baseline simulations (1980-2014) revealed substantial yield gains with elevated nitrogen application: compared to the 90 kg N/ha control, treatments of 150 kg N/ha and 200 kg N/ha increased yields by 1,263 kg/ha and 1,326 kg/ha, respectively, during the 2030-2100 projection period. Climate-driven yield variability exhibited marked spatiotemporal heterogeneity, with annual mean increases under 90 kg N/ha fertilization reaching 1,111 kg/ha (SSP1-2.6) and 1,018 kg/ha (SSP5-8.5) relative to baseline conditions. These findings highlight the dual role of adaptive nitrogen management and climate-resilient land-use planning, providing actionable insights to maximize the ecological and agricultural returns of soil-water conservation initiatives while safeguarding long-term food security in this vulnerable agroecosystem. Bangladesh J. Bot. 54(3): 841-853, 2025 (September) Special